A inflexão zapatista: o Congreso Nacional Indígena e a candidatura presidencial em 2018 - Simone da Silva Ribeiro Gomes; Guilherme Figueredo Benzaquen (Ciências Sociais Unisinos, 2018)
This text discusses the announcement of support by the Zapatista Army of National Liberation (EZLN) to the Mexican presidential elections of 2018 by the Congreso Nacional Indigena (CNI). Drawing from the analysis of 31 speeches of EZLN, initiated with the announcement of the candidature and following CNI documents, we will discuss central issues for the analysis of this social movement, active since 1994, like the relationship of this movement with the State and the choice of an indigenous woman as their candidate. Additionally, we will discuss usual interpretations on the zapatista project and their political constructions. This article has two main objectives, firstly, to analyze the proposed candidature by EZLN and CNI, understanding some possible internal and external consequences of this decision, and to observe the main actors’ moves on the Mexican and international political scenario after this proposition.